Leadership & management of machining : how to integrate technology, robust processes, and people to win! - Tarvin, Patrick (Hanser Publishers ; Hanser Publications, 2016)
The intent of all technological advancements in the machining universe is to increase productivity and precision with less involvement of the endangered species known as the Machinist. Connectivity, data, and digitization are providing opportunities for significant improvements in modeling, programming, simulation, machine/people productivity, and real-time decision making. Advances in chip technology and processing speeds yield more sophisticated controls. Software enhancements create advanced CAM systems which interpret more complex models and produce higher precision programs. This book demonstrates how to integrate these technological advancements with Lean /Six Sigma, CNC Programming, Quality, and machining best practices to create an agile machining organization capable of winning against competition anywhere in the world. While most publications are written for executives the author has deliberately designed this publication for the entire organization. The role of everyone on the organizational chart or in the shop is discussed and reviewed. The premise of the book is that the demands of global competition on the modern machining organization are so great that success requires a foundation of Leadership, People, Equipment, Quality, IT, robust processes, and all employees executing to yield exceptional quality, delivery, and profits. The author provides the architecture and blueprint for high performance.